Terapi Aktivitas Kelompok Tebak Gambar Pada Klien Lansia Dengan Demensi Untuk Memenuhi Kebutuhan Stimulasi Sensori Di UPTD Perlindungan Sosial Provinsi Banten - Rachmawati, Annisa Ena; Sari, Rina puspita; Nurhasanah, Cucu; Mahasari, Denida; Noviana, Diana; Herawati, Herti Eka; Nurlaela, Marisah; Yeni, Neng; Aprilia, Sonia; Kulsum, Umi; Mulyani, Utami (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Aging leads to cognitive decline, particularly in elderly individuals with dementia, affecting their memory, orientation, and ability to process information. Sensory stimulation through therapeutic approaches plays a crucial role in maintaining cognitive function and improving quality of life in geriatric care. Objective: The purpose of this service was to enhance cognitive function in elderly individuals with dementia through Group Activity Therapy (GAT) using Picture Guessing, aiming to improve memory, concentration, and social interaction. Method: This public service was conducted at the UPTD Social Protection Unit of the Banten Province Social Service. Sixteen elderly participants were selected based on cognitive screening using the Mini-Mental State Examination (MMSE) and Short Portable Mental Status Questionnaire (SPMSQ). The therapy involved interactive picture-guessing activities to provide sensory stimulation and cognitive training. Result: The intervention showed positive outcomes, with participants demonstrating improved memory retention, increased concentration, and higher engagement in social interactions. Observations indicated that structured sensory stimulation through Picture Guessing Therapy contributed to cognitive enhancement. Conclusion: Group Activity Therapy using Picture Guessing proved effective in stimulating cognitive function in elderly individuals with dementia.